Uma abordagem para suporte à decisão clínica baseada em semântica no domínio da nefrologia - Tavares, Esaú Alencar (2016)
In health area, the orientations and guidelines for clinical practice are being projected to improve the quality of healthcare and reduce the use of unnecessary, inefficient or harmful interventions. In this atmosphere, approaches for Clinical Decision Support, using as knowledge base the representation of the information restrained in these guidelines, may usufruct of a guide for making inferences based on decisions, actions and validated clinical recomendations, helping with quality the provision of healthcare. The adequate nephrological identification and attendance of patients with Chronic Kidney Disease (CKD) have been appreciated as important opportunities to block its progression and unfavorable outcome, as the mortality. Since these situations are generally of progressive, insidious and asymptomatic evolution, there are difficulties related to its diagnosis, staging and routing, overloading the specialists doctors' work. In face of these facts, this work’s aim was to propose the development of an approach of Clinical Decision Support, based on semantics and logic, to help the ones that work in the Primary Attention of health, in the decision making related to the diagnosis and staging of CKD, searching this way to give support to the appropriate routing to the nephrology specialists. The approach proposed the creation and use of a knowledge base which was based on OntoDecideDRC, an ontology of domain that represented the knowledge related to the purposes of the approach. This approach was implemented in shape of a prototype of web service, where avaliation methods were applied with help of a specialist doctor of the area, through the utilization of competence issues and clinical cases. This study contributes to the comprehension of the methods related to the development of approaches of support to decision using as knowledge base an ontology in the health area. At the end, this approach provides informations about valid recommendations, in order to promote the quality in the medical healthcare related to the disease under study. These informations are in a shape that is capable of being shared, updated, and reused by others systems or approaches in the area.